Assessment of Radiation Dose and Excessive Life Time Cancer Risk from the Exposed Sandstones of Siwalik Rocks System in the Tamman Area of Pakistan - Qureshi, A. A.; Manzoor, S.; K. Jadoon, I. A.; Waheed, A.; Rana, A. N. (The Nucleus, 2015)
Siwalik System of rocks is exposed all along the Himalayan foothills from Assam to Baluchistan for about 4000 km. The Siwalik System of rocks is composed of sandstones and shales. Intermittent uranium mineralization is known in Siwalikâ€™s sandstones in India and Pakistan and is productive uranium horizon in Pakistan. Specific activities of 226Ra, 232Th and 40K were measured in the Siwalikâ€™s sandstones exposed in Tamman area using high purity (HPGe) ï§- ray spectrometer. The average activity concentration of 226Ra, 232Th and 40K was found to be 15.93, 25.58 and 450.97 Bqkg-1 respectively. The radiation indices were also assessed which are well below the worldâ€™s averages. The outdoor and indoor excessive life time cancer risk was calculated as 0.18x10-3 and 1.35 x10-3 . The Siwalikâ€™s sandstones have no excessive life time cancer risk to the local population and sand derived from the Siwalikâ€™s sandstone is a safe building material.